Customer Accounting as One of the Strategic Management Accounting Tools and its Impact on Performance in E-Retail Stores - Abdel Halim, Abeer M. M. (The Arab Journal of Administration, 2025)
The study aims to determine the impact of management accounting practices associated with analyzing and managing relationships with customers in electronic retail stores on the performance of these companies, expressed in the annual revenues. The study was applied on a big Saudi Retail Company, which has more than 50 branches all over the kingdom, beside a very distinguished online shopping website and mobile shopping application since 2011.The required data was extracted from financial reports and reports of boards of directors published for three consecutive years, as well as through interviews and inquiries from company officials. The management accounting practices associated with customer analysis techniques, their behavior and interaction through the company’s e-shopping website have contributed to increasing the volume of electronic transactions and then, increasing the company’s revenues. It should be noted that the integration between the marketing information related to the customer analysis, techniques of data analysis on the electronic retail platforms, and the accounting practices needed for planning, control and evaluation still need to be developed in Saudi electronic retail stores to achieve the value added for the company expressed in increasing the gross profitability.